2013
DOI: 10.1021/ja402424j
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Free Palladium-Mediated Site-Specific Protein Labeling Inside Gram-Negative Bacterial Pathogens

Abstract: Palladium, a key transition metal in advancing modern organic synthesis, mediates diverse chemical conversions including many carbon-carbon bond formation reactions between organic compounds. However, expanding palladium chemistry for conjugation of biomolecules such as proteins, particularly within their native cellular context, is still in its infancy. Here we report the site-specific protein labeling inside pathogenic Gram-negative bacterial cells via a ligand-free palladium-mediated cross-coupling reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
155
0
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(163 citation statements)
references
References 103 publications
0
155
0
8
Order By: Relevance
“…It was also shown that PEG chains offer new reactivity and a significant enhancement in rate as self-liganding (internally chelating) boronic acids when used with Pd(OAc) 2 to give a high-yielding site-specific PEGylation of proteins 128 . This self-liganded effect has more recently been exploited by Li et al 130 , who found that PEG-conjugated fluorophores with Pd(NO 3 ) 2 could efficiently catalyse the Sonogashira crosscoupling, even intracellularly, in E. coli and Shigella.…”
Section: Review Nature Communications | Doi: 101038/ncomms5740mentioning
confidence: 99%
“…It was also shown that PEG chains offer new reactivity and a significant enhancement in rate as self-liganding (internally chelating) boronic acids when used with Pd(OAc) 2 to give a high-yielding site-specific PEGylation of proteins 128 . This self-liganded effect has more recently been exploited by Li et al 130 , who found that PEG-conjugated fluorophores with Pd(NO 3 ) 2 could efficiently catalyse the Sonogashira crosscoupling, even intracellularly, in E. coli and Shigella.…”
Section: Review Nature Communications | Doi: 101038/ncomms5740mentioning
confidence: 99%
“…Attracted by the compatibility and applications of Pd species and bacteria [11 ,18], Chen reported ligand-free palladium-mediated site-specific protein labelling inside Gram-negative bacteria [28]. Here Pd(NO 3 ) 2 was used as a simple, efficient and biocompatible reagent for fluorescent labelling of target proteins via a copper-free Sonogashira coupling reaction.…”
Section: Homogenous Pd-mediated Chemistrymentioning
confidence: 99%
“…Similarly, this Review will not cover the click chemistries catalyzed by palladium for bioconjugation of purified proteins or in cells. 529,530 4.12.3.2.2. Staudinger−Bertozzi Ligation.…”
Section: Targeting Genetically Encoded Ketone Handlesmentioning
confidence: 99%